Progestin-Primed Ovarian Stimulation Protocol for Patients With Endometrioma - Yang, Ai-Min; Feng, Teng-Fei; Han, Yan; Zhao, Zhi-Ming; Wang, Wei; Wang, Yi-Zhuo; Zuo, Xiao-Qi; Xu, Xiuhua; Shi, Bao-Jun; Li, Lipeng; Hao, Gui-Min; Cui, Na (Frontiers in Endocrinology, 2022)
Objective: To evaluate the pregnancy outcomes of progestin-primed ovarian stimulation (PPOS) protocol for patients with endometrioma underwent in vitro fertilization / intra-cytoplasmic sperm injection embryo transfer (IVF/ICSI-ET). Design: Observational retrospective cohort study. Setting: University affiliated reproductive center Study participants: 605 infertile patients with endometrioma underwent IVF/ICSI-ET from January 2016 to March 2021 were included in this study. Methods: The primary outcome was live birth, the secondary outcomes were implantation rate, biochemical pregnancy, clinical pregnancy and ongoing pregnancy. Results: Compared to PPOS protocol, the probability of implantation showed no significant difference between ultra-long gonadotrophin-releasing hormone agonist (GnRHa) protocol and gonadotrophin-releasing hormone antagonist (GnRHant) (OR 1.7, 95% CI 0.9-3.1, OR 1.2, 95% CI 0.7-2.1, respectively). The ultra-long GnRHa protocol was correlated with a significantly higher biochemical pregnancy and clinical pregnancy than PPOS protocol in the multivariable logistic regression analysis (OR 2.3, 95% CI 1.1-4.9, OR 2.4, 95% CI 1.1-5.3, respectively). However, no significant difference was found in terms of biochemical pregnancy, clinical pregnancy and ongoing pregnancy between PPOS and GnRHant protocol (OR 1.4, 95% CI 0.7-2.7, OR 1.3, 95% CI 0.7-2.4, OR 1.1, 95% CI 0.6-2.3, respectively). In addition, compared to PPOS protocol, ultra-long protocol and GnRHant protocol showed no statistical difference in ongoing pregnancy (OR 2.0, 95% CI 0.9-4.5). Notably, the ultra-long protocol was associated with an increased probability of live birth than PPOS protocol both in crude analysis and multivariable logistic regression analysis (OR 2.6, 95% CI 1.3-5.1, OR 2.5, 95% CI 1.1-5.7, respectively). Nevertheless, there was no statistical difference in live birth between PPOS and GnRHant protocol either in crude analysis and multivariable logistic regression analysis (OR1.2, 95% CI 0.6-2.3, OR 1.2, 95% CI 0.6-2.5, respectively). Conclusions: Based on the reproductive outcomes of the first ET cycles in patients with endometrioma, PPOS protocol may associated with inferior reproductive outcomes in terms of biochemical pregnancy, clinical pregnancy and live birth than ultra-long protocol. However, there was no significant difference in implantation rate, clinical pregnancy, ongoing pregnancy and live birth between PPOS and GnRHant protocol.